The Potential for Sustainable Harvest of Common Persimmon (Diospyros virginiana L.) fruits at Pea Ridge National Military Park - Moody, Jennifer; Kindscher, Kelly (Ethnobotany Research and Applications, 2022)
Background: The large, sweet fruits of the Common Persimmon (Diospyros virginiana L.) have a long history as a wild-harvested food in the eastern United States, by both Indigenous people and European settlers. However, little is known about the sustainability of persimmon fruit harvest. Persimmon fruits are a culturally important food for the Osage Nation. Pea Ridge National Military Park (hereafter PERI) is within the Osage ancestral territory Methods: We examine the sustainability of persimmon fruit harvest through field surveys of fruit production and the application of the United Plant Savers “At-Risk Assessment Tool”, which assesses the risk of overharvesting wild plants. Our field work to determine persimmon fruit yield was conducted at PERI in response to a National Park Service’s (NPS) 2016 rule which provides a pathway for Native American tribes, the Osage Nation in our case, to collect culturally important plants from NPS land if harvest is sustainable. Results: Combining our field surveys of fruit production with NPS data on persimmon tree density and potential persimmon habitat at PERI, we estimate annual fruit production of about 143,000 persimmon fruits, or about 1,990 kg (4100 lbs.) at PERI. Persimmon fruit harvest has a low risk of overharvest, with an At-Risk score of 19 on a scale with a max score of 96 (highest risk). Conclusions: An annual harvest of 9-15 kgs ( 20-30 lbs.) of persimmon fruit by the Osage at PERI (< 1% of total estimated yield), would be sustainable and help promote traditional Osage practices of collecting, preserving, and eating persimmons. Keywords: persimmon, sustainable harvest, At-Risk assessment, Pea Ridge, ethnobotany